Mechanisms of Ferroptosis and Relations With Regulated Cell Death: A Review - Lei, Pengxu; Bai, Tao; Sun, Yuling (Frontiers in Physiology, 2019)
Ferroptosis is a newly identified form of nonapoptotic regulated cell death (RCD) characterized by iron-dependent accumulation of lipid peroxides. It is morphologically and biochemically different from known types of cell death. Ferroptosis plays a vital role in the treatment of tumors, renal failure and ischemia reperfusion injury (IRI). Inhibition of glutathione peroxidase 4 (GPX4), starvation of cysteine and peroxidation of arachidonoyl (AA) trigger ferroptosis in the cells. Iron chelators, lipophilic antioxidants and specific inhibitor prevent ferroptosis. Although massive researches have demonstrated the importance of ferroptosis in human, its mechanism is not really clear. In this review, we get out of this mess by dividing the processes that induce ferroptosis into two aspects: processes that facilitate the formation of lipid peroxides and processes that suppress the reduction of lipid peroxides. At the same time, we summarize the relations between ferroptosis and several types of cell death.